Software Network Lookout Net Monitor For Employees Sebagai Media Pembelajaran Kkpi Klas X SMK N 1 Pedan - Suhartana . (Indonesian Journal of Networking and Security (IJNS), 2013)
Education is always evolving world has undergone many changes. Among them, the learning method is not only using the conventional method, but also by using a more modern way, as an example of media-based learning with multimedia. In addition to the various advantages it has attracted many students, especially students Vocational High School 1 Pedan (SMK Negeri 1 Pedan). SMK Negeri 1 Pedan is a school that has majoring in Business Management and Computer and Information Technology all classes taught KKPI mater. In this class taught Introduction to Computers and Application Software. But in the learning process experienced some problems, students are less able to understand what is taught in schools because of the limited time teachers in providing material and they do not optimize learning facilities while at school. Therefore we need a breakthrough to overcometheseproblems. The purpose of this study was generated media instructional media software NETWORK.LOOKOUT.NET.MONITOR EMPLOYEES AS A MEDIA FOR TEACHING CLASS X KKPI SMK N 1 PEDAN TAHUN 2012 which presents an interactive learning model with an attractive and easy to learn, can be used in the classroom, can also be used as a classroom teacher instructional media attention and interest in learning the material KKPI students when teaching in the classroom and to improve the quality of education.   Abtraksi: Dunia Pendidikan yang selalu berkembang telah mengalami banyak perubahan. Diantaranya, metode pembelajaran tidak hanya menggunakan cara konvensional, namun juga dengan menggunakan cara yang lebih modern, sebagai contoh media pembelajaran dengan berbasis multimedia. Selain memiliki berbagai keunggulan hal ini banyak diminati siswa khususnya siswa Sekolah Menengah Kejuruan Negeri 1 Pedan (SMK Negeri 1 Pedan). SMK Negeri 1 Pedan adalah sebuah sekolah yang mempunyai jurusan Bisnis Manajemen dan Teknologi Komputer dan informatika semua klas diajarkan mater KKPI. Pada kelas inilah diajarkan Pengenalan Komputer dan Software Aplikasinya. Akan tetapi dalam proses pembelajaran mengalami beberapa masalah, siswa merasa kurang bisa memahami yang diajarkan disekolah dikarenakan keterbatasan waktu guru dalam memberikan materi dan mereka belum mengoptimalkan fasilitas belajar ketika di sekolah. Oleh karena itu diperlukan sebuah terobosan baru untuk mengatasi masalah-masalah tersebut. Tujuan dari penelitian ini adalah dihasilkan media pembelajaran media software NETWORK.LOOKOUT.NET.MONITOR FOR EMPLOYEES SEBAGAI MEDIA PEMBELAJARAN KKPI KLAS X SMK N 1 PEDAN TAHUN 2012 yang menyajikan sebuah model pembelajaran yang interaktif dengan tampilan yang menarik dan mudah dipelajari, dapat dipergunakan didalam kelas, dapat juga digunakan guru kelas sebagai media pembelajaran yang menarik perhatian dan minat belajar siswa ketika mengajarkan materi KKPI di dalam kelas serta dapat meningkatkan mutu